An Image Processor Bill Acceptor for Iraqi Currency - Abbas, Ammar Awni (Al-Nahrain Journal of Science, 2019)
Automatic Teller Machines (ATMs) and vending machines is a rapidly growing trade in the Iraqi market. Bill acceptors, are considered the heart of these machines have a great significance. Due to the inflation in Iraq with numerous forgery attempt to the currency, an efficient way to accept and validate the Iraqi currency is very important. This paper suggests a bill acceptorto accept, recognize the amount, and validate the bill based solely on image processing functions rather than the magnetic field detection that is used in the regular Bill Acceptors. The program couples the faked bill with a photo graph of the person who presents it. The program uses the Matlab computer vision abilities to recognize the bill. The distinctive characteristics that appears on the banknote when an ultraviolet light is shed on the bill it used for the authentication part with the same Matlab pattern recognition functions. The proposed system include all the mechanical and electronical parts that are used in the proposed system. The results was 100% accurate, which implies that there is great possibility to use this technique in industrial bill acceptors.